Mutations Affecting N-Acetylglucosaminidase in Dictyostelium discoideum - Dimond, Randall L. (1973)
A procedure for screening several thousand clones for alterations in a specific gene product was apapplied to mutagenized cultures of Dictyostelium discoideum. Six strains were recovered which had less N-acetylglucosaminidase (EC 3.2.1.30) than the wild type. In addition, we isolated four strains in which the enzyme was temperature-sensitive. The enzyme from one of these strains had an altered substrate affinity. N-Acetylglucosaminidase is present at a low level in cells grown on bacteria and increases up to 10-fold during the aggregation stage of development. The enzyme appears to be essential to maintain migrating pseudoplasmodia of normal size, as shown by the fact that all of the mutant strains which accumulate very little N-acetyl-glucosaminidase formed only small migrating pseudoplasmodia containing less than 10% the number of cells found in the wild-type pseudoplasmodia. The small pseudoplasmodia migrated at less than a third the rate of wild-type pseudoplasmodia and ultimately formed diminutive fruiting bodies. N-Acetylglucosaminidase thus appears to be a developmental enzyme that functions during the migration stage.